Telerehabilitation for People with Chronic Obstructive Pulmonary Disease: Feasibility of a Simple, Real Time Model of Supervised Exercise Training. (June 2013) - Holland, Anne E; Hill, Catherine J; Rochford, Peter; Fiore, Julio; Berlowitz, David J; Mcdonald, Christine F
We evaluated the safety and feasibility of home telerehabilitation for people with chronic obstructive pulmonary disease (COPD). Eight patients with mean age of 66 years and moderately impaired lung function took part. The telerehabilitation equipment in the participant's home included an exercise bicycle, a tablet computer with webcam for low bandwidth videoconferencing, and a pulse oximeter positioned so that the display was visible while videoconferencing. Participants undertook supervised aerobic training twice a week for eight weeks, with two participants and a physiotherapist attending each class via videoconferencing from separate locations. Primary outcomes were adverse events, sessions attended and system usability. Secondary outcomes were the 6-minute walk distance (6MWD) and Chronic Respiratory Questionnaire (CRQ). No significant adverse events occurred during the study. Participants attended 76% of possible sessions. System usability ratings were excellent when sessions were delivered via the university network (mean 94 out of 100) but lower when using the hospital network (mean 59 out of 100), with 67% of technical problems related to data network capability. Five participants completed the programme, with clinically significant improvements in 6MWD (mean 27 m, SD 40) and CRQ dyspnoea (4 units, SD 4). Simple home-based telerehabilitation using readily available equipment is safe and feasible for people with COPD. Effective delivery of telerehabilitation requires an adequate data network.